2021
DOI: 10.1038/s41467-021-24807-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome of bronchoalveolar lavage fluid reveals sequential change of macrophages during SARS-CoV-2 infection in ferrets

Abstract: Few studies have used a longitudinal approach to describe the immune response to SARS-CoV-2 infection. Here, we perform single-cell RNA sequencing of bronchoalveolar lavage fluid cells longitudinally obtained from SARS-CoV-2-infected ferrets. Landscape analysis of the lung immune microenvironment shows distinct changes in cell proportions and characteristics compared to uninfected control, at 2 and 5 days post-infection (dpi). Macrophages are classified into 10 distinct subpopulations with transcriptome change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 40 publications
(51 reference statements)
2
52
0
Order By: Relevance
“…During the acute phase of SARS-CoV-2 infection, macrophages were the most abundant immunocyte population that harbored vRNA in african green monkey lung cells 9 . Similarly, infected ferrets exhibited infiltration of monocyte-derived macrophages and induction of inflammatory responses in the bronchoalveolar lavage 10 . Similar induction of early innate defense responses in acute phase of COVID-19 at 3 dpi with resolution by 7 dpi in the lungs of rhesus macaques, has recently been reported 11 .…”
Section: Discussionmentioning
confidence: 92%
“…During the acute phase of SARS-CoV-2 infection, macrophages were the most abundant immunocyte population that harbored vRNA in african green monkey lung cells 9 . Similarly, infected ferrets exhibited infiltration of monocyte-derived macrophages and induction of inflammatory responses in the bronchoalveolar lavage 10 . Similar induction of early innate defense responses in acute phase of COVID-19 at 3 dpi with resolution by 7 dpi in the lungs of rhesus macaques, has recently been reported 11 .…”
Section: Discussionmentioning
confidence: 92%
“…In addition, a recent single cell RNA sequencing analysis of the bronchial alveolar lavage fluid from ferrets infected with SARS-CoV-2 identified many subpopulations of macrophages at 2 days post-infection. Additional studies are crucial to illustrate how monocytes functionally contribute to viral clearance and late-stage hyperinflammation [ 71 ]. RNA velocity analysis indicated complex kinetics in both M1 and M2 macrophages originated from monocyte-derived macrophages [ 71 ], indicating the complex nature of the macrophage responses.…”
Section: Sars-cov-2 Infection and Host Responsesmentioning
confidence: 99%
“…Additional studies are crucial to illustrate how monocytes functionally contribute to viral clearance and late-stage hyperinflammation [ 71 ]. RNA velocity analysis indicated complex kinetics in both M1 and M2 macrophages originated from monocyte-derived macrophages [ 71 ], indicating the complex nature of the macrophage responses.…”
Section: Sars-cov-2 Infection and Host Responsesmentioning
confidence: 99%
“…Many studies have confirmed that attenuated antiviral responses and inappropriate inflammatory responses exist in COVID‐19 patients, including persistently enriched T cells and monocytes. 97 , 98 SARS‐CoV‐2 infects alveolar macrophages to induce the production of T cell chemoattractants, and lead to the activated T cells. Then, the activated T cells began to produce interferon‐γ (IFN‐γ), and IFN‐γ will promote the release of inflammatory cytokines, including T cell chemoattractants, from alveolar macrophages in turn, and resulted in further T cell activation.…”
Section: Application Of Transcriptomics In Covid‐19 Pandemicmentioning
confidence: 99%